Key factors behind productivity trends in EU countries (European Central Bank (ECB), 2021)
The aim of this report is to foster a better understanding of past trends in, and drivers of, productivity growth in the countries of the European Union (EU) and of the interplay between productivity and monetary policy. To this end, a group of experts from 15 national central banks and the European Central Bank (ECB) joined forces and pooled data and expertise for more than 18 months to produce the report. Group members drew on the extensive research already conducted on productivity growth, including within the European System of Central Banks and in the context of the review of the ECB's monetary policy strategy, and worked together to conduct new analyses.After recalling the key facts and figures, the report looks into the predominant drivers of productivity growth in firms, with a focus on technology as a key determinant of aggregate productivity dynamics. It then discusses the main factors behind resource reallocation both across incumbent firms and as a result of the entry and exit of firms. Although productivity is a real-economy phenomenon and its evolution predominantly hinges on the structural features of the economy and national policies, the report also raises the question of the extent to which, and under what circumstances, monetary policy may affect productivity. In addition, it places productivity in a broader perspective by taking into account other important structural trends that are expected to have an impact on productivity in the medium-to-long run, such as globalisation, population ageing, climate change and digitalisation. Finally, the report considers the possible impacts of the coronavirus (COVID-19) pandemic on productivity in EU countries. ...
Keywords: D22; D24; D61; O33; O47; O52; 330; Productivity growth; European Union; drivers and policy implications